The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/1980-5373-mr-2020-0268
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Wear, Friction Behavior and Characterization of Carbon Fiber Reinforced Epoxy Composites for Transport Applications

Abstract: Thermoplastics are finding the place in the current industrial sector due to its load bearing capacities. In this research, With the aid of pin on disc test set up, adhesive and abrasive wear behavior of leaf spring materials 30% short carbon fiber reinforced epoxy (SF), 30% long carbon fiber reinforced epoxy (LF) as well as Unreinforced epoxy (UF) are evaluated for automobile applications. Under multi pass abrasive wear condition, the effect of fiber reinforcement on plastic energy of deformation, matrix crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Suthan et al 109 studied the influence of four different biofillers on the sliding wear behavior of epoxy‐based NFRHCs, that is, rice, wheat, coconut shell powder, and ground nutshell powder, and demonstrated that 30 wt% of filler content showed the better wear characteristics. Sudhagar and Kumar 110 addressed the wear characteristics of bauhinia racemose‐based polyester composites. Composites comprising 5% and 20% by weight of fibers are observed to be more wear‐resistant and can be utilized as automotive gears in automobiles.…”
Section: Wear Behavior Of Nfrhcsmentioning
confidence: 99%
“…Suthan et al 109 studied the influence of four different biofillers on the sliding wear behavior of epoxy‐based NFRHCs, that is, rice, wheat, coconut shell powder, and ground nutshell powder, and demonstrated that 30 wt% of filler content showed the better wear characteristics. Sudhagar and Kumar 110 addressed the wear characteristics of bauhinia racemose‐based polyester composites. Composites comprising 5% and 20% by weight of fibers are observed to be more wear‐resistant and can be utilized as automotive gears in automobiles.…”
Section: Wear Behavior Of Nfrhcsmentioning
confidence: 99%